The effect of students of sports management and coaching education department on entrepreneurial tendencies of career plans - Mustafa Vural; Yaşar Çoruh (Institute of Advanced Engineering and Science, 2019)
This study investigated the effect of career planning of the students in the Ağrı Ibrahim Çeçen University department of sports management and the coaching education department on entrepreneurial tendencies. The research group consisted of 161 students who studying in Ağrı Ibrahim Çeçen University Sports Management and Coaching Department. In the study,